Genologiczne eksperymenty w „Miłosierdziu” i „Strasznych dzieciach” Karola Huberta Rostworowskiego - Dąbrowska, Aleksandra (Zagadnienia Rodzajów Literackich, 2023)
The author analyses Karol Hubert Rostworowski’s Miłosierdzie and Straszne Dzieci through the prism of genre studies and distinguishes several formal solutions connected with genres such as mystery play, commedia dell’arte, morality play, nativity scene, circus or tableau vivant. The analysis demonstrates that not only had Rostworowski used the mentioned genres, but also transformed them to determine the very perception of events taking place on the scene. This technique of manoeuvring separate genres in Miłosierdzie is based on both combining and contrasting them, which enabled the playwright to create a tragicomic character of the play. However, in Straszne Dzieci he hyperbolized genres in order to construct an on-scene grotesque. Turns out, Rostworowski’s creative output is centred around the sublime and the tragic just as much as the comic and the ironic. Besides, metatheatrical techniques, which encouraged the audience to think of Rostworowski’s works in an analytical manner, are yet another important aspect of the two plays associated with the listed genres. Therefore, the great genre experiment executed by Rostworowski in the 1920s cannot be simplified into ordinary games with conventions. The playwright has endeavoured to break the usual schemes of perception among his audience, redefining their judgements on mankind, history, and religion. The author argues that the analysis of the two plays is crucial in Rostworowski’s studies as well as in the discussion on the development of the entirety of dramatic works during the interwar period. The technique of combining and transforming conventional genres could be seen in the outputs of many playwrights throughout the 20s and 30s, nevertheless, it was Rostworowski who became one of the first precursors of said technique in the Polish dramatic field.